2021
DOI: 10.46918/equals.v4i2.979
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Pemecahan Masalah Matematis Ditinjau dari Tingkat Self-Efficacy

Abstract: Kemampuan Pemecahan masalah matematis sangat penting karena merupakan salah satu kompetensi utama yang harus dimiliki siswa dalam proses berpikir matematika. Penelitian ini bertujuan untuk mendeskripsikan kemampuan pemecahan masalah matematis ditinjau dari tingkat self-efficacy siswa SMP. Jenis penelitian ini yaitu studi kasus dengan metode deskriptif kualitatif. Teknik pengumpulan data yang digunakan yaitu berupa pemberian angket self-efficacy, tes kemampuan pemecahan masalah, dan wawancara. Subjek penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…On both indicators, the high self-efficacy student can understand problems, solve problems correctly and re-examine the answers. This is in line with the research results by Rahmawati et al (2021), Wijayanti et al (2021), which mention that students who have high self-efficacy perform all stages of problem-solving when solving a problem. With high self-efficacy, students can solve problems well (Askar et al, 2016).…”
Section: Resultssupporting
confidence: 91%
“…On both indicators, the high self-efficacy student can understand problems, solve problems correctly and re-examine the answers. This is in line with the research results by Rahmawati et al (2021), Wijayanti et al (2021), which mention that students who have high self-efficacy perform all stages of problem-solving when solving a problem. With high self-efficacy, students can solve problems well (Askar et al, 2016).…”
Section: Resultssupporting
confidence: 91%
“…In addition, subjects with self-efficacy are also able to present situations mathematically using variables, symbols, and diagrams to solve numeracy problems. This is in line with the results of the study by Rahmawati et al, (2021) that students with a low level of self-efficacy are only able to fulfil only one problem solving indicator, namely understand the problem.…”
Section: Figure 5 Cinta's Answer To Questionsupporting
confidence: 90%
“…[47] Chasani et al & Rahmawati et al revealed that students with self-efficacy were fulfilling two indicators namely writing down known information and solving problems according to plan. [48,49] In addition, the flipped classroom learning model helps develop self-efficacy and student learning outcomes, so that students' mathematical problem-solving abilities also increase significantly. [50]…”
Section: Analysis Of Students' Mathematicalmentioning
confidence: 99%